Applications of inorganic nanoparticles in biological electron microscopy - Ni, Thomas Wentung, author; Ackerson, Christopher, advisor; Prieto, Amy, committee member; Finke, Richard, committee member; Peersen, Olve, committee member (Colorado State University. Libraries, 2016)
Electron microscopy is an immensely powerful for imaging at the cellular level. However, many of the macromolecules of interest are difficult to image due to low electron density. There has been an immense body of work in order to visualize these macromolecules. In the past, many of the methods of visualization revolved around staining samples with heavy metals, however these stains are non-specific. In order to develop more specific methods of tagging macromolecules, there are two different methods to consider: the first being a top-down approach, in which electron dense tags, in this case inorganic nanoparticles, are given specific ligands to take advantage of different chemistries to attach these nanoparticles to macromolecules of interest. The second method is through a bottom-up approach where biomolecules are given the specific ability to form inorganic nanoparticles. Inorganic nanoparticles have been investigated with various ligands in order to enhance binding capability to macromolecules. The chief method of functionalizing these inorganic nanoparticles comes from ligand exchange; much has been studied regarding ligand exchange, but there are still many unanswered questions. Herein, we endeavor to reveal both the mechanism of exchange and the functional unit of exchange. We also report progress towards understanding an enzyme that is capable of forming inorganic nanoparticles, which could be cloned onto proteins as well. This bottom up style has been studied in several other groups; however, none of the previously reported methods have seen much use. Herein, we report a potential NADPH-dependent enzyme that forms selenium nanoparticles.